Электроимпульсный способ бурения скважин и буровое долото - Муратов В. М. Василий Михайлович; Важов В. Ф. Владислав Фёдорович; Лопатин В. В. Владимир Васильевич; Дацкевич С. Ю. Сергей Юрьевич; Журков М. Ю. Михаил Юрьевич; Гафаров Р. Р. Руслан Ринатович
опубл. 22.10.12